Leaders and Followers Algorithm for Balanced Transportation Problem - Helen Yuliana Angmalisang; Harrychoon Angmalisang; Sylvia Jane Sumarauw (Computer Engineering and Applications Journal, 2023)
Leaders and Followers algorithm is a metaheuristic algorithm which uses two sets of solutions and avoid comparison between random exploratory sample solutions and the best solutions. In this paper, it is used to solve the balanced transportation problem. There are some modifications in the proposed algorithm in order to fit the algorithm to the problem. The proposed algorithm is evaluated using 138 problems. The results are better than the results obtained by other algorithm from previous studies. Overall, Leaders and Followers algorithm has no difficulty in finding optimal solution, even in problems that have large dimension, number of supply and number of demands.